Decades-Old Discovery: Misplaced CuT Uncovered During Hysterectomy - Dixit, Anjani; Hood, Mitesh Mohan (Medicine and Medical Research: New Perspectives Vol. 4, 2024)
Introduction: Intrauterine contraceptive devices are vital for long-term contraception, but their potential complications, such as migration and embedment, can present diagnostic challenges. Case Presentation: We present a case study of a 51-year-old woman with symptoms of excessive menstrual bleeding and recurrent abdominal pain. Despite initial ultrasound indications of an IUCD, further evaluations suggested a potential endometrial mass. Hindered by obesity-related imaging limitations, comprehensive clinical assessments guided management decisions. Conclusion: The patient opted for laparoscopic hysterectomy, revealing a surprising finding: a misplaced copper intrauterine device embedded within the uterine fundus. This case emphasizes the complexities in diagnosing intrauterine abnormalities and underscores the importance of thorough evaluation and patient-centered care in treatment planning.